THE CLINICAL COURSE OF GASTRITIS AND ITS MODERN SOLUTIONS AMONG PRIMARY SCHOOL-AGED STUDENTS - Rasulova Saodat Khalimovna (Modern American Journals, 2025)
This scientific article describes the clinical course, pathogenesis, risk factors, and modern approaches to diagnosis and treatment of gastritis in primary school children. The study was conducted among children aged 7–11 years and examined the role of diet, stress, infectious factors, and H.pylori bacteria in the development of gastritis. Clinical signs, laboratory and instrumental diagnostics were analyzed. The effectiveness of modern treatment methods, including eradication therapy, diet therapy, and psychological correction, was evaluated. The results of the study showed that complex therapy is highly effective in children with gastritis.
Keywords: Gastritis, children's gastroenterology, clinical course, H.pylori, diagnosis, treatment, prevention, junior school age.